(untitled) (Economic and Political Thought, 2016)
The analysis of open economy in a short term both in the theory of economics and education has a very strong foundation in the IS-LM-BP Model, which has limitations that have a fundamental practical importance in the context of the European integration. Namely, the model does not allow for a monetary union case study. Because of that, it is worth looking closely at the analysis of the domestic and foreign economy, which is possible within the model of the two economies. Broadening the perspective onto two entities allows not only for observation of the effects of macroeconomic shocks in the two economies but also for a detailed analysis of mechanisms responsible for the transmission of shocks from one country to another. In addition, the approach based on two economies let the author develop a completely new model of two countries functioning in the conditions of a monetary union, which allows for an analysis of shock transmission that is not possible in case of a model with a fixed currency exchange rate. The presented model of two economies functioning in the conditions of a monetary union also has educational advantages connected with its simplicity in comparison with a model of two big economies. The analysis of the models of two big economies with flexible currency exchange rate and economies in a monetary union shows considerable differences in the functioning of the two group types. The differences concern not only the effects of macroeconomic shocks (both real and nominal) in the analysed countries but also the way of transmitting shocks from one country to another.